EFFECTS OF GEOPHYSICAL BIASES IN GNSS POSITIONING USING STATIC PPP METHOD - Sandyana Halim - Nim: 151 13 079, Khaidir
GNSS positioning requires multiple correction of errors to achieve precise solution. Some of the errors could be reduced by using differencing method. Unfortunately, such a method cannot be conducted in Precise Point Positioning (PPP) technique, because it only uses a single receiver. Some of these errors that need to be corrected in PPP are the earth rotation and time difference between signal transmission and reception, relativistic clock error, ocean loading, pole tide and earth tide. In this research, each correction is calculated using a self-made MATLAB program. The results explain that characteristics of the earth rotation and time difference between signal transmission and reception error may displace satellite coordinates up to 200 meters, relativistic clock error can change distance measurement data as large as 12 meters, ocean loading, pole tide, and earth tide errors can displace receiver coordinates up to 1.5 centimeters, 2 millimeters, and 20 centimeters, respectively.